Development and application of rock rheological constitutive model considering dynamic stress field and seepage field - Yian Chen; Guangming Zhao; Wensong Xu; Shoujian Peng; Jiang Xu (International Journal of Mining Science and Technology)
The generalized rheological tests on sandstone were conducted under both dynamic stress and seepage fields. The results demonstrate that the rheological strain of the specimen under increased stress conditions is greater than that under creep conditions, indicating that the dynamic stress field significantly influences the rheological behaviours of sandstone. Following the rheological tests, the number of small pores in the sandstone decreased, while the number of medium-sized pores increased, forming new seepage channels. The high initial rheological stress accelerated fracture compression and the closure of seepage channels, resulting in reduction in the permeability of sandstone. Based on the principles of generalized rheology and the experimental findings, a novel rock rheological constitutive model incorporating both the dynamic stress field and seepage properties has been developed. Numerical simulations of surrounding rock deformation in geotechnical engineering were carried out using a secondary development version of this model, which confirmed the applicability of the generalized rheological numerical simulation method. These results provide theoretical support for the long-term stability evaluation of engineering rock masses and for predicting the deformation of surrounding rock.